Single-incision mini-slings: obturator complex pull-out-force measurements - Lenz, Florian; Doll, Sara; Sohn, Christof; Brocker, Kerstin A. (Gynecologic and obstetric investigation, 2017)
Aim: To evaluate the different pull-out-force out of the obturator membrane and the obturator internus muscle of 2 mini-sling systems for stress urinary incontinence (SUI) treatment. Material and Methods: In a prospective study, the pull-out-force measurements were performed on 8 female cadaver pelvises, both on the obturator membrane and internal muscle, using the force measurement device PCE-FM50 (PCE Instruments). Tested were the hooks of 2 on the market available mini-sling kits (MiniArc by American Medical System; Ajust by BARD Inc.). Connected to the force measurement device, the hooks were placed into the obturator membrane and the obturator internus muscle. Mean value and SD were documented. Results: On the complete obturator complex, Ajust showed a significantly higher pull-out-force (2,561.75 ± 638.8 g) than did the MiniArc (1,780.69 ± 442.3 g), p = 0.025. No significant differences were performed on the obturator membrane. Conclusions: The Ajust mini-sling hook is, given the objective results, more stably attached to the obturator complex than the MiniArc. Yet, both systems are sufficiently attachable to the evaluated anatomic structures, fulfilling the needed requirements for their use in the treatment of SUI.